Koordersiochloa Merr. (Gramineae), the correct name for Streblochaete Hochst. ex Pilg - Veldkamp, Jan Frits (REINWARDTIA, 2012)
Streblochaete Hochst. ex Pilg. (Gramineae) was not validly published in 1906, but in 1927. Koordersiochloa Merr. (1917) is therefore the correct name. Two new combinations are made.ÃÂ